Croissance urbaine et accessibilité : intérêts et limites de l’approche par les densités dans une perspective de modélisation de l’usage du sol - Patrick Bonnel (Unité Mixte de Recherche 8504 Géographie-cités, 2013)
Land-Use and transport interaction models today take an important role as decision-making tools, especially in a context marked by the reinforcement of economical, energy and environmental constraints. If the estimation of transport demand and accessibilities in these models depends on densities, these densities are often viewed as exogenous. This paper intends to render them endogenous by measuring the effect of accessibilities on intra-urban densities in the urban area of Lyon in 1990, 1999 and 2006, and defining an evolution law over time for the coefficients of the model. The successive relax of the hypothesis of spatial homogeneity and monocentrism which characterize the Bussière model and the improvement of the transport cost measure (distance from the center of the urban area, generalized time, gravity accessibility to jobs) give good static results but do not allow to predict the evolutions of the population densities at the district level. The selective movements of peri-urbanization and return to the center that were stressed during this short time are far from being explained by the evolution of accessibility to the center or to jobs in the urban area. The distribution of densities in this monocentric city depends not only on the accessibility to jobs but also appear to be structured by the centrality and the distribution of the social and spatial amenities, which in part result from the urban policy and the macro-agents’ decisions.